Pediatric Shock: An Uncommon and Underrecognized Etiology - Derespina, Kim R.; Kaushik, Shubhi; Medar, Shivanand S. (Journal of Pediatric Intensive Care, 2020)
Kawasaki disease, also known as mucocutaneous lymph node syndrome, is a well-known disease entity. Kawasaki shock syndrome (KSS), on the other hand, is less well recognized and has been reported in small single-center international studies and case reports. We report a case in the United States of an 11-year-old male with multiorgan failure and shock, presumed to be secondary to toxic shock but later diagnosed with KSS, an underrecognized entity in the US and review the literature. KSS should be considered in a critically ill child with unexplained shock.
Keywords: Kawasaki disease; Kawasaki shock syndrome; erythema